Type 2 Diabetes, Pre-Diabetes, and the Metabolic Syndrome - Codario, Ronald A.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana Press, 2011)
Diagnosing and managing type 2 diabetes presents an enormous challenge to the primary care provider confronted with multiple emerging scientific insights, therapeutic strategies and risk reduction principles. In Type 2 Diabetes, Pre-Diabetes, and the Metabolic Syndrome: The Primary Care Guide to Diagnosis and Management, Second Edition, Ronald A. Codario, M.D., FACP -- a well-known and highly respected authority on diabetes -- details the state-of-the-art in diagnosing, managing and attenuating risks in patients with this disease. Utilizing his extensive experience in private practice, medical education and clinical research for over 35 years, Dr. Codario explains in simple clinical terms, the current understanding of the pathophysiology of diabetes, the latest clinical trials, developing controversies, updates on new medications and an expanded section on Special Populations. With his unique, multiple board certifications in clinical hypertension, vascular medicine, internal medicine, vascular ultrasound and clinical lipidology, Dr. Codario provides practical guidelines for treatment with insulin and oral agents, lipid and hypertension control and comprehensive risk reduction strategies. Extensively reviewed are the metabolic syndrome, the role of exercise and nutrition, and key issues associated with herb and nutriceutical use. Illustrative case studies in diabetes management, an outstanding bibliography of suggested readings, and extensive chapter subheadings for quick reference make this book a practical, easy-to-read guide for dealing with this killer disease. Type 2 Diabetes, Pre-Diabetes, and the Metabolic Syndrome: The Primary Care Guide to Diagnosis and Management, Second Edition is the direct result of many years of listening, teaching, lecturing and empathizing with fellow primary care providers and their patients in the ongoing fight against diabetes. Like the internationally acclaimed first edition, this is a must read and invaluable guide for all primary care providers, students, caregivers and patients battling the ravages of this ever increasing epidemic.
Pathophysiology of Type-2 Diabetes -- Guidelines and Classifications -- Exercise -- Nutrition -- Obesity and the Metabolic Syndrome -- Oral Agents for Type-2 Diabetes -- Insulin Use -- Non- Insulin Injectables -- Macrovascular Disease -- Microvascular Disease -- Diabetic Dyslipidemia -- Hypertension in Diabetics -- The Pathophysiology and Metabolic Impact of Hyperglycemia -- RIsk Reduction in the Diabetic Patient -- Special Populations -- Resources.
Keywords: Medicine; Family medicine; Internal medicine; Emergency medicine; Medicine & Public Health; Primary Care Medicine; Internal Medicine; General Practice / Family Medicine; Medicine/Public Health, general